Trauma-focused treatment for traumatic stress symptoms in unaccompanied refugee minors: a multiple baseline case series - Van Es, Carlijn Maria; Velu, Merel E.; Sleijpen, Marieke; van der Aa, Niels; Boelen, Paul A.; Mooren, Trudy (Frontiers in Psychology, 2023)
Introduction: Unaccompanied refugee minors (URMs) are at increased risk of developing mental health problems, such as symptoms of posttraumatic stress disorder (PTSD) and depression. In addition, URMs face several barriers to mental health care. Few studies have evaluated trauma-focused interventions for URMs that target these issues. The current study evaluated a multimodal trauma-focused treatment approach for URMs. It aimed to provide an initial indication of the effectiveness of this treatment approach and to provide a qualitative evaluation assessing treatment satisfaction of the participating URMs. Methods: A mixed-methods study was conducted among ten URMs, combining quantitative data with qualitative data through triangulation. Quantitative data were collected using a non-concurrent multiple baseline design in which repeated, weekly assessments were carried out during a randomized baseline period, during treatment, and during a 4-week follow-up period. Questionnaires assessing PTSD (Children’s Revised Impact of Event Scale) and symptoms of depression (The Patient Health Questionnaire-9, modified for adolescents) were used. In addition, treatment satisfaction was measured post-treatment using a semi-structured interview. Results: During the qualitative evaluation, all but one URM noted they found the trauma-focused treatment approach useful and felt the treatment had positively impacted their wellbeing. However, the results of the quantitative evaluation did not show clinically reliable symptom reductions at posttest or follow-up. Implications for clinical practice and research are discussed. Discussion: The current study presents our search in developing a treatment approach for URMs. It adds to the current knowledge about methodological considerations in evaluating treatments for URMs, the potential effects of trauma-focused treatments on URMs, and the implementation of treatments for URMs.